A positive electrode composition, positive electrode material and secondary battery

By using a combination of functional particles, dispersants and cross-linking agents in the LFP electrode, a three-dimensional cross-linked network structure is formed, which solves the problem of the existing LFP electrode being unable to ensure the flexibility of the pole piece when increasing the thickness and compaction, and achieves a better High energy density and longer cycle life.

CN118970054BActive Publication Date: 2025-01-21SHENZHEN HAODYNE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411442384.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

While increasing the thickness and compaction, existing LFP electrodes cannot ensure the flexibility of the electrode sheet, resulting in the impact of the battery energy density and overall performance.

Method used

A positive electrode composition is used, including functional particles, a dispersant and a cross-linking agent. The dispersing agent has a polymer chain segment and an anchoring group. The polymer chain segment overcomes the van der Waals attraction between the functional particles and the cross-linking agent Form a three-dimensional cross-linked network structure to improve the bonding force between particles and the flexibility of the pole piece.

Benefits of technology

It improves the solid content and coating efficiency of the positive electrode slurry, enhances the cohesion and flexibility of the pole piece, avoids the problem of material falling out of the pole piece during winding or die-cutting, and improves the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

At present, the energy density of LFP batteries can be improved by the design concept of thick electrode and high compaction, but flexibility cannot be ensured. The present invention provides a positive electrode composition, a positive electrode material and a secondary battery. The positive electrode composition includes functional particles, a dispersant and a cross-linking agent, and the functional particles include positive electrode active materials and / or conductive agents; the dispersant includes a polymer segment and an anchoring group connected to the polymer segment, and the polymer segment includes an acrylate-polyol unit, and the anchoring group includes one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group. The positive electrode composition provided in the present application is provided by adding a cross-linking agent to allow free radical polymerization between the dispersant and the functional particles when the positive electrode composition forms a positive electrode material layer, thereby forming a three-dimensional cross-linked network structure to provide cohesion and flexibility of the positive electrode sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode composition, a positive electrode material and a secondary battery. Background Art

[0002] Secondary batteries have the advantages of high voltage, high specific energy, stable discharge voltage, good cycle performance, good safety performance, and long working life. They are widely used in power vehicles, energy storage and other fields. Lithium-ion batteries in secondary batteries include lithium iron phosphate systems. Lithium iron phosphate (LFP) batteries are the mainstream system for energy storage and power batteries because of their advantages such as good safety, long cycle life and low cost. However, the LFP battery system is limited by the material structure and voltage platform, resulting in its low energy density. The methods for improving the energy density of LFP batteries in the prior art include improving the specific capacity of LFP materials, optimizing the battery design or module design, and improving the energy density of battery packs. The main way to improve the specific capacity of LFP materials is to nano-size the materials and modify LFP by carbon coating and ion doping. However, the modified nano-scale LFP particles have a large specific surface area and are easy to agglomerate during the pulping process. At the same time, there are also problems such as easy moisture absorption causing the slurry to gel, which leads to abnormalities in the subsequent coating process and affects the yield and performance of the battery.

[0003] To solve this problem, dispersants are usually added to the LFP slurry to improve the dispersion effect of the slurry. However, conventional LFP slurry cannot meet the flexibility requirements of the pole pieces under the thick electrode and high compaction system. The thick electrode setting increases the coating surface density to increase the energy density of the battery. However, after increasing the coating surface density through rolling, the pole pieces become more brittle and the flexibility cannot meet the standards. The pole pieces may fall off during die cutting in the lamination process and winding of the battery cells, which further affects the energy density and overall performance of the battery.

[0004] Therefore, designing an LFP slurry to improve the LFP solid content and slurry stability in the slurry while ensuring the flexibility of the electrode under the thick electrode design is an urgent problem to be solved. Summary of the invention

[0005] The present invention aims at the problem that the existing positive electrode cannot ensure the flexibility of the pole piece while increasing the thickness and compaction of the LFP electrode. The present invention provides a positive electrode composition, a positive electrode material and a secondary battery.

[0006] In order to solve the above technical problems, the present invention provides a positive electrode composition, which includes functional particles, a dispersant and a cross-linking agent, wherein the functional particles include positive electrode active materials and / or conductive agents; the dispersant includes a polymer segment and an anchor group connected to the polymer segment, the polymer segment includes an acrylate-polyol unit, and the anchor group includes one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group.

[0007] Preferably, the cross-linking agent contains at least two acrylate groups in its structure.

[0008] Preferably, the crosslinking agent includes one or more of diethylene glycol dimethacrylate, ethylene glycol diacrylate, tetra(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol diacrylate, 1,6-hexanediol dimethacrylate, and pentaerythritol tetraacrylate.

[0009] Preferably, the molar ratio of the crosslinking agent to the dispersant is (0.1-0.3):1.

[0010] Preferably, the terminal group of the polymer chain segment is an acrylate group; and the dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and a monomer containing an anchor group.

[0011] Preferably, the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate;

[0012] And / or, the anchor group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, cyanoacetamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, stearyl methacrylate, ethylene glycol, and ethylene glycol monomethyl ether.

[0013] Preferably, the molecular weight of the polymer chain segment is 10000-20000 g / mol, and the Tg of the dispersant is 25° C.-45° C.

[0014] Preferably, the surface of the positive electrode active material and / or the conductive agent is modified with a silane coupling agent containing a double bond;

[0015] The silane coupling agent containing double bonds includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.

[0016] In a second aspect, the present application provides a positive electrode material, which is prepared from the positive electrode composition described in any one of the above items, and the positive electrode material includes functional particles, polymer segments and a cross-linked structure, the polymer segments include acrylate-polyol units, and the cross-linked structure is used for cross-linking of polymer segments on adjacent functional particles, and cross-linking of polymer segments with functional particles.

[0017] In a third aspect, the present application provides a secondary battery, comprising a negative electrode sheet, an electrolyte and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode material layer is prepared from the positive electrode composition as described above. Or the positive electrode material layer is the positive electrode material as described above. Beneficial Effects

[0018] The dispersant in the positive electrode composition of the present application has a polymer chain segment and an anchoring group. The polymer chain segment overcomes the van der Waals attraction between the functional particles, reduces the problems of high discharge viscosity and high viscosity growth during the standing process caused by the large specific surface area of ​​the small-particle LFP main material and the nano-scale conductive agent, thereby increasing the solid content of the positive electrode slurry and improving the coating efficiency and yield.

[0019] In particular, the structure of the dispersant provided in the present application has an end group that is an acrylate group. By adding a cross-linking agent to the positive electrode composition, the acrylate group at the end of the dispersant is polymerized by itself or reacts with other double-bonded groups in the positive electrode composition (such as double bonds in a silane coupling agent containing double bonds) to form a cross-linked structure, thereby forming a three-dimensional cross-linked network structure inside the positive electrode composition. This can improve the adhesion between particles in the positive electrode composition, thereby improving the cohesion and flexibility of the electrode coating, avoiding the occurrence of electrode shedding during winding or die-cutting, which reduces the yield of battery cell preparation, and at the same time improves the life of the battery cell during the cycle process.

[0020] The coating of the positive electrode sheet in the secondary battery of the present application is prepared from the above-mentioned positive electrode composition, and a three-dimensional cross-linked network structure is formed by a cross-linking agent, a dispersant and functional particles, thereby improving the flexibility and cohesion of the positive electrode sheet, so that the positive electrode sheet meets the thick electrode design, further improving the energy density of the secondary battery. DETAILED DESCRIPTION

[0021] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] An embodiment of the present application provides a positive electrode composition, which includes functional particles, a dispersant and a cross-linking agent, wherein the functional particles include a positive electrode active material and / or a conductive agent; the dispersant includes a polymer segment and an anchor group connected to the polymer segment, the polymer segment includes an acrylate-polyol unit, and the anchor group includes one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group.

[0023] The dispersant in the positive electrode composition provided in the present application has a polymer segment and an anchoring group. The polymer segment overcomes the van der Waals attraction between the functional particles and reduces the viscosity effect of the conductive agent, thereby increasing the solid content of the positive electrode slurry and improving the coating yield.

[0024] In particular, the structure of the dispersant provided in the present application has an end group that is an acrylate group. By adding a cross-linking agent to the positive electrode composition, the acrylate group at the end of the dispersant is polymerized by itself or reacts with other double-bonded groups in the positive electrode composition (such as double bonds in a silane coupling agent containing double bonds) to form a cross-linked structure, thereby forming a three-dimensional cross-linked network structure inside the positive electrode composition, which can improve the cohesion of the coating formed by the positive electrode composition and the flexibility of the electrode piece, thereby avoiding material falling off during winding or die-cutting of the electrode piece.

[0025] In some embodiments, the crosslinking agent contains at least two acrylate groups in its structure. The acrylate groups in the crosslinking agent react with the double bonds in the dispersant and the functional particles or between the dispersant itself, thereby forming a three-dimensional crosslinked network structure between the functional particles and the dispersant, thereby improving the cohesion and flexibility of the positive electrode sheet containing the positive electrode composition.

[0026] In a preferred embodiment, the cross-linking agent structure contains at least three or four acrylate groups, so that the positive electrode composition forms a higher cross-linking density and ensures a higher cohesive force.

[0027] In some embodiments, the crosslinking agent includes one or more of diethylene glycol dimethacrylate, ethylene glycol diacrylate, tetraethylene glycol diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol diacrylate, 1,6-hexanediol dimethacrylate, and pentaerythritol tetraacrylate. By selecting the above crosslinking agent to react with the dispersant and the functional particles, the positive electrode composition forms a higher crosslinking density and ensures a higher cohesive force.

[0028] In some embodiments, in the positive electrode composition, the molar ratio of the crosslinking agent to the dispersant is (0.1-0.3): 1. Specifically, the molar ratio of the crosslinking agent to the dispersant includes but is not limited to 0.1: 1, 0.15: 1, 0.2: 1, 0.25: 1, or 0.3: 1. By adding a crosslinking agent of appropriate mass, the dispersant and the functional particles in the positive electrode composition form a three-dimensional crosslinked network.

[0029] In some embodiments, the terminal group of the polymer chain segment is an acrylate group; and the dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and an anchor group-containing monomer.

[0030] Specifically, the acrylate-polyol monomer has acrylate groups at both ends, wherein the acrylate group at one end reacts with the anchor group monomer, and the acrylate group at the other end can be used for self-polymerization through a cross-linking agent and for reacting with lithium iron phosphate / conductive agent modified with a double bond-containing silane coupling agent through the cross-linking agent.

[0031] Furthermore, the dispersant can be obtained by conventional double bond polymerization reaction, and the specific reaction conditions are easily known to those skilled in the art. For example, the preparation method includes the following steps:

[0032] Mix ethanol as a solvent, an anchor group-containing monomer, and an acrylate-polyol monomer under nitrogen, and stir to obtain a mixed solution;

[0033] The mixed solution was heated to 50-80° C. under a nitrogen atmosphere, and then an initiator, azobisisobutyronitrile, was added, and the mixture was kept warm with continuous stirring. The reaction was stopped after 24 hours of reaction, and then the ethanol was removed by heating and rotary evaporation to obtain a dispersant.

[0034] In some embodiments, the molar ratio of the anchoring group-containing monomer to the acrylate-polyol monomer is (10-50): (30-90). The acrylate-polyol monomer forms the acrylate-polyol unit in the polymer segment, and the molecular weight of the polymer segment in the dispersant is controlled by limiting the mass ratio of the acrylate-polyol monomer to the anchoring group-containing monomer. By limiting the molecular weight of the polymer segment in the dispersant, on the one hand, the anchoring group in the dispersant itself is prevented from having a bridging effect that fails to achieve a dispersion effect, and on the other hand, a certain steric hindrance effect is generated by limiting the polymer segment, thereby improving the dispersion effect between the functional particles. At the same time, by limiting the molecular weight of the polymer segment, the glass transition temperature of the dispersant is adjusted, thereby achieving better flexibility.

[0035] Specifically, the molar ratio of the anchor group-containing monomer to the acrylate-polyol monomer includes, but is not limited to, 10:30, 50:90, 25:50, 20:30, 50:50 or 50:80.

[0036] In some embodiments, the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate. By selecting the above-mentioned acrylate-polyol monomers, it is convenient to control the length and steric hindrance of the polymer chain segments in the dispersant, thereby adjusting the dispersion effect.

[0037] In some embodiments, the anchoring group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, cyanoacetamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, stearic methacrylate, ethylene glycol, and ethylene glycol monomethyl ether. By introducing the above-mentioned anchoring group into the structure of the dispersant, on the one hand, the anchoring group is easy to combine with the hydroxyl group on the treated aluminum foil, thereby increasing the bonding force between the coating formed by the positive electrode composition and the aluminum foil, and enhancing the peeling force between the coating and the aluminum foil. On the other hand, the anchoring group disperses the functional particles well by reacting with the dispersed functional particles to form covalent bonds or ionic bonds. At the same time, the anchoring group can improve the wettability of the pole piece and the electrolyte, thereby reducing the internal resistance of the battery and improving the performance of the battery cell.

[0038] In a preferred embodiment, the molecular weight of the polymer segment is 10000-20000 g / mol, and the Tg of the dispersant is 25°C-45°C. By regulating the molecular weight of the polymer segment and thus the chain length of the polymer segment, on the one hand, the van der Waals attraction between the functional particles (lithium iron phosphate and conductive carbon black) is overcome, thereby adjusting the dispersing properties of the dispersant. On the other hand, the glass transition temperature Tg of the formed dispersant is regulated. g , to improve the flexibility of the pole piece.

[0039] If the molecular weight of the polymer chain segment is too small, the anchoring group in the dispersant will have a "bridging" effect, and the purpose of dispersing the functional particles cannot be achieved. At this time, Tg is higher than 45°C.

[0040] If the molecular weight of the polymer chain segment is too large, the polymer molecules of the dispersant will easily fold back on themselves, forming a large steric hindrance. The steric hindrance causes the anchoring group to be unable to anchor the functional particle surface well, causing the slurry to flocculate, resulting in poor dispersion of the final positive electrode slurry. At this time, Tg is lower than 25°C.

[0041] When the molecular weight of the polymer chain segment is within the above range, the "bridging" effect of the anchoring group in the dispersant can be avoided, and the anchoring group can be better anchored on the surface of the functional particles, and the Tg is relatively moderate, at 25°C~45°C, thereby achieving better reinforcement effect and better flexibility performance.

[0042] In some embodiments, the surface of the positive electrode active material and / or the conductive agent is modified with a silane coupling agent containing a double bond. The positive electrode active material can be various active materials commonly used in the art, for example, it can be lithium iron phosphate (LFP). The conductive agent can be various conductive agents commonly used in the art, for example, carbon nanotubes (CNTs), conductive carbon black (SP) or conductive graphite (KS-6).

[0043] The surface of lithium iron phosphate or the surface of conductive carbon black is modified by a silane coupling agent containing double bonds, so that the double bonds on the surface of the modified lithium iron phosphate or the modified conductive carbon black react with the dispersant through a cross-linking agent, ensuring that the modified lithium iron phosphate or the modified conductive carbon black and the dispersant achieve the dispersion stability of the positive electrode slurry through steric hindrance, anchoring functional groups and the like, thereby increasing the solid content of the positive electrode slurry. At the same time, the modified lithium iron phosphate or the modified conductive carbon black is combined with the dispersant through a cross-linking agent or the dispersant is polymerized by the cross-linking agent, so that the cohesion and flexibility of the coating formed by the positive electrode composition are enhanced.

[0044] In some embodiments, the silane coupling agent containing a double bond includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.

[0045] In the present invention, the method for obtaining the lithium iron phosphate and the conductive agent whose surface is modified with a silane coupling agent containing a double bond is well known to those skilled in the art. For example, they can be directly purchased or prepared by themselves. Furthermore, the method for modifying the lithium iron phosphate and the conductive agent with a silane coupling agent containing a double bond is as follows:

[0046] NMP (N-methylpyrrolidone) as a solvent is mixed with a silane coupling agent containing a double bond, and stirred to obtain a mixed solution. LFP is added to the mixed solution, and after pre-mixing, it is dispersed at a high speed to obtain LFP modified with a silane coupling agent containing a double bond.

[0047] NMP as a solvent and a silane coupling agent containing a double bond are mixed and stirred to obtain a mixed solution, SP is added to the mixed solution, and after pre-mixing, the SP modified with a silane coupling agent containing a double bond is dispersed at a high speed to obtain the SP.

[0048] In some embodiments, the positive electrode composition further includes a coupling agent and a binder, wherein the mass of the coupling agent accounts for 0.02% to 0.05% of the mass of the functional particles. The mass of the dispersant accounts for 0.05% to 0.5% of the mass of the functional particles, and the conductive agent accounts for 1% to 2% of the solid mass of the positive electrode composition components. The binder accounts for 1.2% to 2.5% of the solid mass of the positive electrode composition components.

[0049] The binder may be a common positive electrode binder in the art, such as polyvinylidene fluoride (PVdF), etc. The coupling agent is preferably the aforementioned silane coupling agent containing a double bond.

[0050] In the second aspect, an embodiment of the present application provides a positive electrode material, which is prepared from the positive electrode composition described in any one of the above items, and the positive electrode material includes functional particles, polymer segments and cross-linked structures, the polymer segments include acrylate-polyol units, and the cross-linked structure is used for cross-linking of polymer segments on adjacent functional particles, and cross-linking of polymer segments with functional particles.

[0051] Specifically, the cross-linked structure is formed by the reaction of the cross-linking agent with the polymer chain segments and the functional particles.

[0052] In the third aspect, an embodiment of the present application provides a secondary battery, including a negative electrode sheet, an electrolyte and a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode material layer is prepared from the positive electrode composition as described above. A three-dimensional cross-linked network structure is formed by a cross-linking agent, a dispersant and functional particles, thereby improving the flexibility and cohesion of the positive electrode sheet, so that the positive electrode sheet meets the thick electrode design, and further improves the energy density of the secondary battery.

[0053] The present invention is further described below by way of examples.

[0054] The positive electrode composition, positive electrode material and secondary battery disclosed in the present invention are specifically described.

[0055] Example 1

[0056] Dispersants

[0057] 350 parts of ethanol, 25 parts of acrylonitrile and 50 parts of poly(ethylene glycol) diacrylate were mixed under nitrogen and stirred at a speed of 50 r / min for 30 seconds to obtain a mixed solution;

[0058] The mixed solution was heated to 50°C under a nitrogen atmosphere, and then 1.5 parts of azobisisobutyronitrile was added, the temperature was kept at 50°C, and stirring was continued at a speed of 50 r / min. The reaction was stopped after 24 hours. 250 parts of N-methylpyrrolidone were added to the obtained polymer solution and heated and rotary evaporated to remove ethanol to obtain a dispersant with a molecular weight of 10000~20000 g / mol, T g It is 41℃.

[0059] Cathode slurry

[0060] The positive electrode slurry includes 98 parts of positive electrode composition and 2 parts of binder polyvinylidene fluoride (PVdF, Arkema HSV900), the positive electrode composition includes 0.02 parts of coupling agent vinyltrimethoxysilane, 96.73 parts of lithium iron phosphate modified, 1 part of conductive carbon black modified with vinyltrimethoxysilane, 0.2 parts of dispersant, and 0.05 parts of cross-linking agent pentaerythritol tetraacrylate.

[0061] The binder and the dispersant are mixed to form a glue solution, vinyltrimethoxysilane-modified lithium iron phosphate and vinyltrimethoxysilane-modified conductive carbon black are added to the glue solution, and the mixture is stirred to obtain a mixed solution, pentaerythritol tetraacrylate is added to the mixed solution as a cross-linking agent, and the positive electrode slurry is obtained after dispersion, and the mass solid content of the positive electrode slurry is 68.25% (the slurry viscosity standard is 6000±1000 cP).

[0062] Preparation of positive electrode

[0063] The positive electrode slurry was coated on both surfaces of the positive electrode current collector Al foil (single layer coating surface density 240 g / m 2 ), then dry, observe the surface appearance of the pole piece (whether it is cracked), and then cold press, the compaction density is 2.4g / cm 3 After processes such as slitting and cutting, the positive electrode sheet is obtained.

[0064] Preparation of negative electrode

[0065] 96% of negative electrode active material graphite, 1% of negative electrode conductive agent conductive carbon black, 1.5% of thickener sodium carboxymethyl cellulose and 1.5% SBR emulsion were mixed, and deionized water was added for stirring to prepare negative electrode slurry. Then the negative electrode slurry was coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, the negative electrode sheet was obtained.

[0066] Secondary battery preparation

[0067] The negative electrode sheet, separator (PE film), and positive electrode sheet are wound in sequence so that the separator is placed between the positive and negative electrodes to play an isolating role, and the electrode assembly is made. The electrode assembly is placed in an outer package, and commercially available electrolyte is injected and packaged. After that, a secondary battery is obtained through processes such as liquid injection, formation, and exhaust.

[0068] Example 2

[0069] Most of the steps of Example 2 are the same as those of Example 1, except that the crosslinking agent is ethylene glycol diacrylate. The mass solid content of the positive electrode slurry is 68.15%.

[0070] Example 3

[0071] Most of the steps of Example 3 are the same as those of Example 1, except that the crosslinking agent is acrylic acid. The mass solid content of the positive electrode slurry is 68.30%.

[0072] Example 4

[0073] Most of the steps of Example 4 are the same as those of Example 1, except that the amount of the crosslinking agent added is 0.01 parts of pentaerythritol tetraacrylate. The mass solid content of the positive electrode slurry is 68.03%.

[0074] Example 5

[0075] Most of the steps of Example 5 are the same as those of Example 1, except that the amount of the crosslinking agent added is 0.1 parts of pentaerythritol tetraacrylate. The mass solid content of the positive electrode slurry is 68.18%.

[0076] Example 6

[0077] Most of the steps of Example 6 are the same as those of Example 1, except that the raw material composition of the dispersant includes 90 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, the molecular weight of the dispersant is 20000-30000 g / mol, and T g is 18℃.

[0078] The mass solid content of the positive electrode slurry is 65.02%.

[0079] Example 7

[0080] Most of the steps of Example 7 are the same as those of Example 1, except that the raw material composition of the dispersant includes 30 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, the molecular weight of the dispersant is 2000-10000 g / mol, and T g The temperature is 48° C. The mass solid content of the positive electrode slurry is 64.9%.

[0081] Example 8

[0082] Most of the steps of Example 8 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 50 parts of acrylonitrile, the molecular weight of the dispersant is 10000-20000 g / mol, and T g The temperature is 43° C. The mass solid content of the positive electrode slurry is 66.96%.

[0083] Example 9

[0084] Most of the steps of Example 9 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 10 parts of acrylonitrile, the molecular weight of the dispersant is 10000-20000 g / mol, and T g The temperature is 42° C. The mass solid content of the positive electrode slurry is 64.09%.

[0085] Example 10

[0086] Most of the steps of Example 10 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate and 25 parts of acrylamide, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 35° C. The lithium iron phosphate is modified by 3-(trimethoxymethylsilyl) propyl acrylate, and the conductive carbon black is modified by 3-(trimethoxymethylsilyl) propyl acrylate. The mass solid content of the positive electrode slurry is 67.9%.

[0087] Embodiment 11

[0088] Most of the steps of Example 11 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate and 25 parts of ethyl acrylate, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 37°C. The lithium iron phosphate is modified by allyltrimethoxysilane, and the conductive carbon black is modified by allyltrimethoxysilane. The mass solid content of the positive electrode slurry is 67.95%.

[0089] Example 12

[0090] Most of the steps of Example 12 are the same as those of Example 1, except that the raw material composition of the dispersant includes 100 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, the molecular weight of the dispersant is 35000-40000 g / mol, and the Tg is 15° C. The mass solid content of the positive electrode slurry is 65.32%.

[0091] Embodiment 13

[0092] Example 13 is similar to Example 1 in most of the steps, except that the raw material composition of the dispersant includes 20 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, the molecular weight of the dispersant is 600-1900 g / mol, and T g The temperature is 51° C. The mass solid content of the positive electrode slurry is 64.43%.

[0093] Embodiment 14

[0094] Example 14 is similar to Example 1 in most of its steps, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 60 parts of acrylonitrile, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 45° C. The mass solid content of the positive electrode slurry is 64.56%.

[0095] Embodiment 15

[0096] Example 15 is similar to Example 1 in most of its steps, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 5 parts of acrylonitrile, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 39° C. The mass solid content of the positive electrode slurry is 64.26%.

[0097] Example 16

[0098] Most of the steps of Example 16 are the same as those of Example 1, except that the conductive carbon black is not modified by a silane coupling agent containing a double bond. The mass solid content of the positive electrode slurry is 67.15%.

[0099] Embodiment 17

[0100] Most of the steps of Example 17 are the same as those of Example 1, except that the conductive carbon black and lithium iron phosphate are not modified by a double-bond-containing silane coupling agent. The mass solid content of the positive electrode slurry is 68.12%.

[0101] Comparative Example 1

[0102] Most of the steps of Comparative Example 1 are the same as those of Example 1, except that the dispersant is poly(ethylene glycol) diacrylate. The mass solid content of the positive electrode slurry is 62.91%.

[0103] Comparative Example 2

[0104] Most of the steps of Comparative Example 2 are the same as those of Example 1, except that the positive electrode composition does not contain a cross-linking agent, and the mass solid content of the positive electrode slurry is 67.98%.

[0105] Comparative Example 3

[0106] Comparative Example 3 is similar to Example 1 in most steps, except that the dispersant is N-methylpyrrolidone dispersion of polyvinylpyrrolidone. The mass solid content of the positive electrode slurry is 64.85%.

[0107] Slurry, pole piece, electrical performance test:

[0108] The slurries, positive electrode sheets, and secondary batteries prepared in the above examples and comparative examples were subjected to the following tests.

[0109] 1) Slurry solid content: Spread the slurry evenly on the surface of aluminum foil, bake and heat it using a solid content meter until it stops losing weight, and record the data at this time.

[0110] 2) Slurry viscosity: The viscosity value is measured at room temperature using a rotational viscometer, 4# rotor, 60 rpm; the 24h viscosity is measured after the slurry is sealed and placed in a φ5cm×15cm bottle for 24 hours.

[0111] 3) Positive electrode peel strength test:

[0112] The coated single-sided positive electrode sheet was heated to 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating was fixed on the tape on the steel plate with the surface facing down. After rolling back and forth 6 times with a 2.5kg roller, the coating and aluminum foil were torn off. The upper plate clamped the aluminum foil side and stretched at a speed of 50mm / min and 180°C. The data of the stable tension section was recorded as the peel strength (N / m).

[0113] 4) Flexibility test

[0114] A tensile testing machine with an existing range of 20N was used, and the machine was switched to the downward pressing mode. The 1.5*12cm cold-pressed pole piece was rolled into a circle and placed in a homemade steel plate fixture. The instrument descending speed was set to 20mm / min. The instrument continuously applied force to the circular pole piece during the downward pressing stroke until the pole piece arc broke. The flexibility of the pole piece can be determined by the downward pressing stroke and the force at the time of breaking.

[0115] 5) Cohesion test

[0116] The coated single-sided positive electrode sheet was heated to 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating side was fixed on the tape on the steel plate with the coating side facing up. After rolling back and forth 6 times with a 2.5kg roller, the coating and aluminum foil were torn off. The upper plate clamped the coating surface and stretched at a speed of 50mm / min and 180℃. The data of the stable tension section was recorded as the peel strength (N / m).

[0117] 6) 25℃, DCIR test

[0118] ① Charge at 0.5C constant current and constant voltage to 3.65V, with a cut-off current of 0.05C; discharge at 0.5C constant current to 2.5V, and record the discharge capacity; repeat the above for 5 weeks, and take the discharge capacity in the 5th week as C0;

[0119] ② Charge at 1C constant current and constant voltage to 3.65V, with a cut-off current of 0.05C; discharge at 1C constant current to 50% SOC, and record the voltage V0 after standing for 2 hours; discharge at 1C constant current for 10s, and record the discharge end voltage V1; charge at 1C constant current for 10S.

[0120] Discharge DCIR = (static terminal voltage V0 before discharge - discharge terminal voltage V1) / discharge current 1C.

[0121] 7) Normal temperature cycle test

[0122] The specific method is: after placing the battery in a constant temperature test room at 25℃±2℃ for 1h, charge it to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C; discharge it to 2.5V at 1C constant current, and record the discharge capacity; repeat the above steps 500 times, and calculate the capacity retention rate.

[0123] The above test results are shown in Table 1 below.

[0124] Table 1

[0125]

[0126] From the above results we can conclude that:

[0127] Compared with the comparative example 1 in which no anchoring group is added, the dispersant obtained by copolymerizing the anchoring group and the polyacrylate in the embodiment 1 has a significant improvement in increasing the solid content of the slurry and maintaining the viscosity stability for 24 hours, and the electrode peeling strength, cohesion and flexibility are greatly improved.

[0128] Compared with Example 1, Example 2 did not add a cross-linking agent, and the pole piece cracked during coating. However, in Example 1, a cross-linking agent was added to form a three-dimensional spatial network cross-linking structure on the surface of the active material and the surface of the conductive agent in the coating, thereby enhancing the cohesion of the coating and the flexibility of the pole piece, so that the pole piece did not crack.

[0129] Compared with Example 1, conventional PVP dispersant is added in Comparative Example 3. Conventional PVP dispersant has no obvious effect on increasing the solid content of the slurry and improving the 24h viscosity stability. The electrode coating cracks and the electrode peeling strength, cohesion and flexibility are all poor, indicating that conventional PVP cannot form a three-dimensional spatial network cross-linking structure on the surface of the active substance and the conductive agent in the coating.

[0130] Examples 1, 2, and 3 respectively compare the effects of cross-linking agents with 4 acrylate functional groups, 2 acrylate functional groups, and 1 acrylate functional group on the degree of cross-linking. It can be seen that the fewer acrylate units in the cross-linking agent, the more obvious the decrease in the flexibility and cohesion of the electrode, which in turn affects the DCIR of the battery cell and the cycle capacity retention rate. This shows that the more acrylate units in the cross-linking agent, the greater the probability of cross-linking, thereby enhancing the three-dimensional network skeleton structure.

[0131] Examples 1, 4, and 5 respectively compare the cross-linking effects of different contents of pentaerythritol tetraacrylate. It can be seen that as the amount of the cross-linking agent used is reduced to 0.01 parts outside the lower limit, the cross-linking probability decreases, and the cross-linking effect is not obvious, resulting in cracking of the pole piece, and decreased flexibility and cohesion; when the amount of the cross-linking agent used is the upper limit of 0.1 parts, although its flexibility and cohesion can be maintained at a high level, the acrylate units in the cross-linking agent will react with the electrolyte components, deteriorate the battery performance, increase the DCIR of the battery cell, and reduce the capacity retention rate.

[0132] Examples 1, 6, 7, 12, and 13 compare the effects of different amounts of polyester on molecular weight. It can be seen that when the proportion of poly(ethylene glycol) diacrylate is too high, the molecular weight is relatively large, and the dispersion of LFP or conductive agent is mainly due to the steric hindrance effect. The effect on the dispersibility and solid content of the slurry is not obvious, and the 24-hour static viscosity of the slurry increases significantly. The flexibility and cohesion of the pole piece also tend to decrease, the DCIR of the battery cell increases, and the cycle capacity retention rate decreases; when the proportion of poly(ethylene glycol) diacrylate is too low, the molecular weight of the dispersant is low, and the pole piece's dispersion and stabilization effect on the slurry is mainly due to the effect of the anchoring group. The increase in the solid content of the slurry is limited, and the 24-hour static viscosity of the slurry increases significantly, which affects the pole piece peeling strength, cohesion, flexibility, DCIR of the battery cell, and cycle performance. Therefore, when the ratio of the anchoring group and the polyester copolymer is moderate, the steric hindrance effect of the dispersant and the ionic bond of the anchoring group can act together on the surface of the dispersed material, thereby increasing the solid content of the slurry and maintaining the slurry stability for 24 hours.

[0133] Examples 1, 8, 9, 14, and 15 compare the effect of the amount of anchoring group acrylonitrile. It can be seen that when the acrylonitrile content is too high, the improvement in the dispersibility of the slurry is mainly due to the effect of the anchoring group, so the increase in the solid content of the slurry is small, and it has a certain effect on the peeling strength, flexibility, and cohesion of the pole piece; when the acrylonitrile content is too low, the improvement in the dispersibility of the slurry is mainly due to the steric hindrance effect of the polyester, resulting in an insignificant increase in the solid content of the slurry, and it has a certain effect on the peeling strength, flexibility, and cohesion of the pole piece. Therefore, when the ratio of the anchoring group and the polyester copolymer is moderate, the steric hindrance effect of the dispersant and the ionic bond of the anchoring group can act together on the surface of the dispersed material, thereby increasing the solid content of the slurry and maintaining the stability of the slurry for 24 hours.

[0134] Examples 1, 10, and 11 compare the effects of other polyesters and anchor groups copolymerized to form dispersants on the slurry solid content improvement, 24h viscosity stability, and electrode properties. The overall differences are not significant, indicating that other polyesters and anchor groups can also achieve similar effects.

[0135] Examples 1 and 16 compare the case where the coupling agent only modifies LFP. In this case, LFP is the main component involved in the subsequent crosslinking. However, since the conductive agent is in close contact with LFP in the active material coating, the polymerization probability of the double bonds of the coupling agent and the crosslinking agent in LFP is reduced, resulting in cracking of the pole piece, and no obvious improvement in the cohesion and flexibility of the coating.

[0136] Examples 1 and 17 compare that if neither LFP nor the conductive agent is modified with a coupling agent, it is impossible to form a three-dimensional network cross-linked structure between the active material LFP and the conductive agent in the coating, thereby failing to improve the flexibility and cohesion of the electrode.

[0137] It can be seen that the dispersant with moderate molecular weight prepared by this method, its steric hindrance effect and the ionic bond of the anchoring group act together on the surface of the dispersed material, so that the slurry has a better dispersion effect, improves the solid content of the slurry and maintains the stability of the slurry for 24 hours; the different contents of acrylate units in the cross-linking agent and the amount added have a certain influence on the probability and degree of cross-linking, which in turn affects the cohesion and flexibility of the electrode, and when the amount of cross-linking agent added is too high, there is a risk of incomplete reaction with the electrolyte, which in turn affects the cycle performance of the battery cell; the active substance and conductive agent modified by the coupling agent can ensure a higher probability of cross-linking with the cross-linking agent, thereby improving the cohesion and flexibility of the electrode, thereby reducing the DCIR of the battery cell and improving the cycle performance of the battery cell.

[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: Prepared from a positive electrode composition, the positive electrode material includes a cross-linked structure, the positive electrode composition includes functional particles, a dispersant and a cross-linking agent, the functional particles include a positive electrode active material and a conductive agent, and the surfaces of the positive electrode active material and the conductive agent are modified with a silane coupling agent containing a double bond; The dispersant comprises a polymer segment and an anchoring group connected to the polymer segment, wherein the polymer segment comprises an acrylate-polyol unit, and the terminal group of the polymer segment is an acrylate group; the anchoring group comprises one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group; the molecular weight of the polymer segment is 10000-20000 g / mol, and the Tg of the dispersant is 25° C.-45° C.; The cross-linked structure is formed by the reaction of a cross-linking agent with polymer segments and functional particles, and is used for cross-linking polymer segments on adjacent functional particles, and cross-linking polymer segments with functional particles.

2. The positive electrode material according to claim 1, characterized in that The crosslinking agent contains at least two acrylate groups in its structure.

3. The positive electrode material according to any one of claims 1 or 2, characterized in that The crosslinking agent includes one or more of diethylene glycol dimethacrylate, ethylene glycol diacrylate, tetra(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol diacrylate, 1,6-hexanediol dimethacrylate, and pentaerythritol tetraacrylate.

4. The positive electrode material according to claim 3, characterized in that The molar ratio of the crosslinking agent to the dispersant is (0.1-0.3):

1.

5. The positive electrode material according to claim 1, characterized in that The dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and a monomer containing an anchor group.

6. The positive electrode material according to claim 5, characterized in that The acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate; And / or, the anchor group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, cyanoacetamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, stearyl methacrylate, ethylene glycol, and ethylene glycol monomethyl ether.

7. The positive electrode material according to claim 1, characterized in that The silane coupling agent containing double bonds includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.

8. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, an electrolyte and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer arranged on at least one side surface of the positive electrode current collector, and the positive electrode material layer is the positive electrode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Positive temperature coefficient (PTC) safe coating as well as preparation method and application thereof

    CN109411760A

  • Binder for positive pole piece, positive pole piece and electrochemical device

    CN115692716A